Neocylindrospermum variakineticum gen. & sp. nov. (Nostocales, Cyanobacteria), a novel genus separated from Cylindrospermum using a polyphasic method. Issue 6 (2nd November 2022) - Tawong, Wittaya; Pongcharoen, Pongsanat; Saijuntha, Weerachai
ABSTRACT: The large genus Cylindrospermum is polyphyletic as currently circumscribed, and its cryptic diversity requires detailed taxonomic evaluation. Two novel cyanobacterial strains were isolated by scraping the surface of wet wood above the water level, in the stream below Mae Phun Waterfall in the northern part of Thailand, and investigated with a polyphasic study combining morphological and molecular analyses. The morphological features of these two novel strains fitted the original description of the genus Cylindrospermum but they differed from known species in cell size, exospore features and akinete formation. Phylogenetic analyses based on 16S rRNA, 16S–23S rRNA ITS region, rpoC1 and nifH genes indicated that the novel strains formed a unique clade with strongly supported values from BI and ML methods. This unique clade was distantly separated from the Cylindrospermum sensu stricto clade and other Cylindrospermum -like clades. Molecular analyses showed that the two novel strains had <96.3% 16S rRNA gene sequence similarity and <83.2% 16S–23S rRNA ITS region sequence similarity to known cyanobacterial genera and other related taxa. Furthermore, ITS secondary structures between the 16S–23S rRNA gene in both strains also exhibited singular folding patterns of D1–D1', Box-B and V3 helix, thereby distinguishing them from the closely related taxa. The establishment of Neocylindrospermum gen. nov . with the type species as N. variakineticum sp. nov . is proposed according to the International Code of Nomenclature for Algae, Fungi, and Plants.